Effects of Curcumin on Vascular Endothelial Growth Factor Expression on Rattus norvegicus Cervical Cancer Xenograft Model - Muninggar, Laili; Widjiati, Widjiati; Yuliati, Indra; Askandar, Brahmana; Hartono, Poedjo (Indonesian Journal of Cancer, 2018)
Objective: To analyze the effect of curcumin in VEGF expression on Rattus norvegicus cervical cancer cell xenograft model.Methods: An experimental study with randomized post test only control group design. The subjects were Rattus norvegicus (Sprague Dawley), inoculated with He-la cervical cancer cells from American Type Culture Collection (ATCC) processed in stem cell laboratory Institute of Tropical Disease (ITD) Airlangga University. 5x106 of He-La cells were injected subcutaneously in dorsal flank area of Rattus norvegicus. After 30 days of observation we performed histopathological examination of xenograft tissue and randomized into 2 groups which were given curcumin orally 1000 mg/kg (curcumin group) vs. no therapy (control group). After another 30 days the xenograft tissue was dissected and underwent immunochemistry examination for VEGF expression.Results: 32 samples of Rattus norvegicus were divided into 2 groups, In curcumin group the VEGF median expression was 2,2 (0,3-7,6) and in control group the VEGF median expression was 6,6 (1,2-12). There was a statistically significant difference with p value =0,009 with Mann Whitney test (p<0,05).Conclusion: VEGF expression in Rattus norvegicus xenograft model of cervical cancer was suppressed by giving Curcumin 1000 mg/kgBB orally.